Use of rapid HIV antibody testing for controlling the HIV pandemic. Issue 6 (December 2005) - Granade, Timothy C
The HIV pandemic continues to expand throughout Africa and southern Asia. Despite recent advances in therapy, the primary means of prevention continues to be the identification of infected patients through diagnostic testing, and the provision of counseling services to reduce HIV transmission. In order to facilitate the identification of infected patients, great strides have been made during the past 10 years towards the development of simple, rapid HIV antibody assays that require no specialized equipment, are relatively stable at ambient temperatures and can be easily performed by people who do not have a laboratory background. Evaluations of these assays have shown that when used in multiple assay algorithm strategies, they perform comparably with current laboratory-based methods. Effective global implementation of these tests will require a concerted effort from public and private health agencies, however, expanding the use of these assays can provide a significant opportunity to slow the devastating spread of HIV.